The status of the video collections of the University of the Philippines Diliman libraries and the information behavior for video materials among the faculty members - Arinuelo, Lileth L. (2012)
This study investigates the present state of the UP Diliman libraries' video collections and how the faculty members utilize different sources, including the library, to fulfill their work-related needs for video materials. Differences in attitude between faculty users and non-users of video materials, and between faculty and librarians were also investigated.